Overexpression of Interleukin-4 in Lungs of Mice Impairs Elimination of Histoplasma capsulatum - Gildea, Lucy A. (American Society for Microbiology, 2003)
Protection against the pathogenic fungus Histoplasma capsulatum requires Th1 cytokines. Since interleukin-4 (IL-4) can inhibit both Th1 cytokine production and activity, we examined the effects of overproduction of IL-4 in the lung on the course of pulmonary histoplasmosis. IL-4 lung transgenic mice manifested a higher fungal burden in their lungs, but not spleens, compared to wild-type infected controls. Despite the higher burden, the transgenic animals were ultimately capable of controlling infection. The adverse effects of IL-4 on H. capsulatum elimination were not observed during the early phase of infection (days 1 to 3) but were maximal at day 7 postinfection, prior to the induction of cell-mediated immunity. Analysis of total body and lung cytokine levels revealed that gamma interferon and tumor necrosis factor alpha production were not inhibited in the presence of excess IL-4. Our results with transgenic mice were supported by additional in vivo studies in which allergen induction of pulmonary IL-4 was associated with delayed clearance of H. capsulatum yeast and increased fungal burden. These findings demonstrate that excess production of endogenous IL-4 modulates protective immunity to H. capsulatum by delaying clearance of the organism but does not prevent the generation of a Th1 response that ultimately controls infection.